Purification and Thermal Stability of Intact Bacillus subtilis Flagella - Dimmitt, K. (1971)
Flagella were prepared and purified in a relatively intact form from bacterial lysates. Immunochemical tests showed that over 95% of the protein in the final preparation consisted of flagellar antigen. These flagella are more stable to thermal denaturation than flagella filaments obtained by shearing. Their thermal properties more closely resemble those of flagella in the native state on bacteria. The presence of the hook structure is responsible for this extra stability.